An outbreak of Getah virus infection among pigs in China, 2017. Issue 3 (25th March 2018) - Yang, T.; Li, R.; Hu, Y.; Yang, L.; Zhao, D.; Du, L.; Li, J.; Ge, M.; Yu, X.
Summary: A Getah virus (GETV) outbreak occurred in a swine farm in Hunan, China, between June and July 2017. Approximately 200 piglets died 5–10 days after birth, and more than 150 pregnant sows had stillbirths or foetal mummies in this outbreak. GETV HuN1, isolated from the cerebrum of an infected piglet, shared a close evolutionary relationship with the Kochi/01/2005 strain, isolated from pigs in Japan. GETV was detected in the cerebral cortices of a dead foetus and in various organs of two infected piglets, thereby demonstrating that GETV can be transmitted through the placenta to infected newborn piglets with multiple tissue tropisms. Seroepizootiologic investigation of GETV revealed that a wide infection of GETV had been persisting in the farm between June 1 and July 17. In conclusion, clinical and laboratory diagnostics of the diseased pigs in this outbreak were consistent with GETV being the causative agent. To the best of our knowledge, this is the first unequivocal report of GETV in pigs in China.